2017
DOI: 10.1002/pon.4406
|View full text |Cite
|
Sign up to set email alerts
|

Developing a mind map–based life review program to improve psychological well‐being of cancer patients: a feasibility study

Abstract: | BACKGROUNDCancer patients often experience psychological distress. Untreated distress causes poor compliance with treatment, prolonged recovery time, poor quality of life, and even increased risk of suicide. 1,2 Life review is a process of recalling, evaluating, and integrating life experiences to facilitate the achievement of ego integrity in the final life stage. 3 Studies have demonstrated its effectiveness in psychological well-being among cancer patients. 4 However, there are still some difficulties enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
0
10
0
3
Order By: Relevance
“…The intervention group received both routine care and the MBLRP. The MBLRP has previously been introduced in detail (Chen et al, ). Briefly, it consisted of four sessions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The intervention group received both routine care and the MBLRP. The MBLRP has previously been introduced in detail (Chen et al, ). Briefly, it consisted of four sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Third, the MBLRP involves looking at albums, listening to music, drawing mind maps and watching videos, which is more engaging than a purely text‐based life review. Our feasibility study has demonstrated that the MBLRP is enjoyable, acceptable and feasible for Chinese cancer patients and it potentially enhances their psychological well‐being (Chen et al, ). This study aimed to examine the effects of the MBLRP on psychological distress, hope, meaning in life and self‐transcendence, with a rigorously designed randomised controlled trial.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…То говори да пацијенти који болују од малигинитета, а третман излечења траје дужи временски период, имају три до четири пута већу шансу да развију психијатријски поремећај. 8 To још једном указује да опоравак од основне болести може бити одложен због придодатог менталног обољења, депресије, емоционалног осиромашења, апатије. 9 Тиме се још једном потврђује мишљење испитаника фокус групе који указју на значај осталих здравствених стручњака у збрињавању ових пацијената.…”
Section: дискусијаunclassified